The Impact of Baseplate Bow on Vacuum Reflow Soldering - 曾雄; 张泉 (Kongzhi Yu Xinxi Jishu)
The impact of IGBT baseplate bow on reflow soldering is analyzed. And the process parameters are adjusted to eliminate the influence of baseplate bow on soldering quality.